Clinical vitamin A deficiency among preschool aged children in southwest Ethiopia - Nuredin, Abdilwahid; Melis, Tamirat; Abdu, Abdu Oumer (Frontiers in Nutrition, 2024)
The clinical manifestations of vitamin A deficiency (VAD) involve night blindness, bitot's spots, corneal xerosis, and corneal scars. It is the most important cause of preventable childhood blindness among children and causes morbidity and mortality. Even though Ethiopia implemented high-potency vitamin A supplements, the occurrence of VAD remains significant.This study was to identify determinants of clinical VAD among preschool-aged children (PSC) in southwest Ethiopia.A community-based survey was conducted among 411 randomly selected PSCs. A pretested and structured questionnaire coupled with clinical observation for signs of vitamin A deficiency by a trained ophthalmologist was used to collect the data. An anthropometric measurement of height was taken and analyzed using WHO Anthro to calculate Z-scores for each index. The public health significance of VAD was declared after comparison with international references. A bi-variable and multi-variable logistic analysis was done. We reported the adjusted odds ratio (AOR), 95% confidence interval, and p-value.Result: A total of 411 children were screened for clinical VAD, and the overall prevalence was 2.2% (95% CI: 1.5-2.5). Of which, night blindness affects 1.2%, bitot's spots affects 0.7%, and corneal xerosis affects 0.2%, indicating a major public health problem compared to the international reference. The odds of clinical VAD were 81% lower among children who received vitamin A supplementation (VAS; AOR = 0.19, 95% CI: 0.04-0.92). On the other hand, PSC of mothers who had attended ANC visits were 89% less likely to develop clinical VAD (AOR = 0.11, P a g e | 2 | 95% CI: 0.02-0.53). In addition, the study revealed that the odds of developing clinical VAD are 82% lower among PSC aged 36 to 47 months (AOR = 0.18; 95% CI: 0.03-0.97).The prevalence of clinical VAD among PSC is a public health problem and is associated with ANC visits, VAS status, and the age of the child, which could be used to target interventions to further reduce existing VAD. Further studies using reliable dietary intake and biomarker data could further depict the burden of subclinical VAD.